108k views
2 votes
PLEASEEE HELPPPPP 88 points!!

PLEASEEE HELPPPPP 88 points!!-example-1
User Yvo
by
5.1k points

2 Answers

3 votes

Answer:

Here's your answer:

3pi/4 =x and 5pi/4 =x

cos x + sqrt(2) = - cos x

subtract cos x from each side

cos x - cosx + sqrt(2) = - cos x - cos x

sqrt(2) = -2 cos x

Divide each side by -2

-sqrt(2) / 2 =-2 cos (x) /-2

-sqrt(2) /2 =cos (x)

Take the inverse cos of each side

cos(-1)(-sqrt(2) /2) =cos^-1(cos (x))

3pi/4 =x and 5pi/4 =x

Explanation:

User Wiml
by
5.0k points
5 votes

Answer:

3pi/4 =x and 5pi/4 =x

Explanation:

cos x + sqrt(2) = - cos x

subtract cos x from each side

cos x - cosx + sqrt(2) = - cos x - cos x

sqrt(2) = -2 cos x

Divide each side by -2

-sqrt(2) / 2 =-2 cos (x) /-2

-sqrt(2) /2 =cos (x)

Take the inverse cos of each side

cos(-1)(-sqrt(2) /2) =cos^-1(cos (x))

3pi/4 =x and 5pi/4 =x

User Bruce Chapman
by
5.7k points